2014
DOI: 10.1111/1469-0691.12582
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of methicillin-resistant Staphylococcus aureus and methicillin-susceptible Staphylococcus aureus carriage in pig farmers: a prospective cohort study

Abstract: Our purpose was to determine the dynamics of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) carriage and its determinants in persons working at pig farms, in order to identify targets for interventions. This prospective cohort study surveyed 49 pig farms in the Netherlands on six sampling dates in 1 year (2010-11). Nasal and oropharyngeal swabs were collected, as well as environmental surface samples from stables and house. Of 110 pig farmers, 38% were persistent MRSA nasal carriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 42 publications
4
57
1
1
Order By: Relevance
“…A study in Switzerland were not detected pig farmers with LA-MRSA [22], in another study in a region of Germany the prevalence was 25% [23]. Our findings are close to those of a study in the Netherlands, where 63% of pig farmers were colonized with the ST398 strain [24]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A study in Switzerland were not detected pig farmers with LA-MRSA [22], in another study in a region of Germany the prevalence was 25% [23]. Our findings are close to those of a study in the Netherlands, where 63% of pig farmers were colonized with the ST398 strain [24]. …”
Section: Discussionsupporting
confidence: 86%
“…Carrier status of LA-MRSA in humans may be related to direct contact with pigs [8] or to human-human transmission [25], and the colonization may be intermittent or persistent [24, 2629]. Therefore, it seems that the risk factors for persistent MRSA-ST398 carrier status depend on the intensity of animal contact [26], together with an age range of 40–49 years, a 40-h working week, and assisting sows with birthing [24].…”
Section: Discussionmentioning
confidence: 99%
“…Verhoeven et al (26) showed that persistent carriers have higher nasal loads (Ͼ10 2 CFU/swab) than intermittent carriers (Ͻ10 2 CFU/ swab). Pig farmers with high nasal MRSA loads have also been shown to be persistent carriers more often than farmers with low MRSA loads (27). It should be noted that counts determined by the MPN method, as was done in the present study, are semiquantitative, and their level of approximation is particularly high for pigs displaying high nasal loads (e.g., between 10,000 and 100,000).…”
Section: Fig 2 Influence Of Farm Pen and Pig On Staphylococcus Aurementioning
confidence: 46%
“…Several animals, particularly pigs and calves, have been documented with MRSA colonization strains [3], and transmission of resistant bacteria from animal to farmers, called livestock-associated MRSA (LA-MRSA), has been demonstrated [4,5]. Interestingly, the prevalence of LA-MRSA strains generally ranges from 20% to 63%, and close contact with animals has been identified as a nasal carriage risk factor for farmers/veterinary workers [6,7].…”
Section: Introductionmentioning
confidence: 99%